An Examination of Sheepskin Effects Over Time - Steffen Habermalz (Institute for the Study of Labor (IZA), 2003)
Previous empirical specifications are not flexible enough to capture the true pattern of sheepskin effects over time. If the quality of the match between the worker and the job contributes to earnings and if higher ability workers more easily reveal their true productivity, sheepskin effects will follow a concave pattern over time. Using the NLSY and measures of actual experience, a variety of specifications (including median regressions) confirm this pattern.
Keywords: I21; J31; I20; 330; returns to education; sheepskin effects; Bildungsertrag; Bildungsniveau; Lohndifferenzierung; Schätzung; Vereinigte Staaten